2008
DOI: 10.1159/000182268
|View full text |Cite
|
Sign up to set email alerts
|

A Severe and Refractory Case of Anti-p200 Pemphigoid Resulting in Multiple Skin Ulcers and Scar Formation

Abstract: Anti-p200 pemphigoid is a recently described autoimmune blistering skin disease that is characterized by the presence of autoantibodies against an unidentified 200-kDa dermal autoantigen. Most of the previous cases have been successfully treated using mild-to-moderate immunosuppressive therapies, which resulted in a good prognosis. We report here a severe and refractory case of anti-p200 pemphigoid that developed in a 53-year-old woman, in which blisters led to multiple skin ulcers, followed by severe scar for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…The autoantibodies mostly target two major components of the DEJ: BP230, also called BPAg1, an intracellular protein of the hemidesmosomal plaque, and BP180, or BPAg2, a transmembrane protein whose dominant epitope is located in the NC16A domain [3]. However, other antigens have been rarely reported in BP, such as in p200 pemphigoid [4]. The pathogenic role of BP180 antibodies in BP has been demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%
“…The autoantibodies mostly target two major components of the DEJ: BP230, also called BPAg1, an intracellular protein of the hemidesmosomal plaque, and BP180, or BPAg2, a transmembrane protein whose dominant epitope is located in the NC16A domain [3]. However, other antigens have been rarely reported in BP, such as in p200 pemphigoid [4]. The pathogenic role of BP180 antibodies in BP has been demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that approximately 25% of patients with anti‐laminin γ1 pemphigoid have reactivity against other autoantigens . Simultaneous autoimmune response to laminin γ1 and BP180 has been reported in four cases including our case, although other three cases did not have psoriasis . This phenomenon may be explained as intermolecular epitope spreading following the inflammatory damage to the BMZ .…”
Section: Discussionmentioning
confidence: 50%
“…2 Simultaneous autoimmune response to laminin c1 and BP180 has been reported in four cases including our case, although other three cases did not have psoriasis. [5][6][7] This phenomenon may be explained as intermolecular epitope spreading following the inflammatory damage to the BMZ. 2,8 Although the etiopathogenesis of psoriasis is unknown, an important role of tumor necrosis factor (TNF)-a-inducible plasmacytoid dendritic cells and T-helper 17 lymphocytes has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery with scarring was occasionally reported in BP cases with IgG autoantibodies to LAD‐1, a case of anti‐laminin gamma‐1 (p200) pemphigoid, and a case of a blistering disease with IgG autoantibodies to BP180, BP230 and laminin‐332 …”
Section: Discussionmentioning
confidence: 99%
“…Recovery with scarring was occasionally reported in BP cases with IgG autoantibodies to LAD-1, 7 a case of anti-laminin gamma-1 (p200) pemphigoid, 8 disease with IgG autoantibodies to BP180, BP230 and laminin-332. 9 The clinical features in our patient mimicked classical EBA.…”
Section: Discussionmentioning
confidence: 99%